Association between alveolar bone loss and serum C-reactive protein levels in aggressive and chronic periodontitis patients - Chopra, Rahul (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: C-reactive protein (CRP) is an acute phase reactant that is produced in response to diverse inflammatory stimuli, and is known predictor of cardiovascular disease risk. Aggressive and chronic periodontitis are two main forms of periodontal disease, which differ mainly in the method of disease progression. This study aims at determining and comparing the relative levels of serum CRP and alveolar bone loss in aggressive and chronic periodontitis patients. MATERIALS AND METHODS: A total of 45 subjects, which were divided into 3 groups diagnosed as having generalized aggressive periodontitis (GAP), chronic generalized periodontitis (CGP) and non-periodontitis controls (NP), were selected for the study. Venous blood samples were collected for quantitative CRP analysis using Turbidimetric immunoassay. Alveolar bone loss (ABL) was measured at proximal sites of posterior teeth on a panoramic radiograph. The relationship between the mean ratio of ABL to root length and serum CRP levels was statistically analyzed using Student unpaired t-test, analysis of variance (ANOVA) and Pearson's correlation coefficient. RESULTS: Mean CRP levels were significantly greater in both GAP (7.49±2.31 mg/l) and CGP (4.88±1.80 mg/l) groups as compared to NP (0.68±0.23 mg/l) with P value <0.0001. The mean value of ABL (%) was 31.58 in CGP group and 36.77 in the GAP group, the difference being statistically significant (P=0.0079). Correlation coefficient between CRP and ABL is 0.9310 in CGP, and 0.9252 in GAP, which indicates a positive correlation between both variables. CONCLUSION: Both forms of periodontitis are associated with increased systemic inflammatory response with aggressiveness of disease progression determining the degree of response.